2015
DOI: 10.1002/adfm.201502360
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Polyelectrolyte Hybridized ZnO Nanoparticles as a Cathode Interfacial Layer for Efficient Polymer Light‐Emitting Diodes

Abstract: IntroductionPolymer light-emitting diodes (PLEDs) have attracted a great attention as a possibility for next-generation large-area display and lighting devices due to solution processability and Herein, we present CPE-hybridized ZnO NPs (CPE:ZnO hybrid NPs), so-called organic/inorganic hybrid material, as a solution-processable CIL for high-effi ciency PLEDs. Alkoxy side-chain tethered polyfl uorene CPE, poly [(9,9-bis((8-(3-methyl-1-imidazolium)octyl)-2,7-fluorene)-alt-(9,9-bis(2-(2-methoxyethoxy)ethyl)-fl uo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…Tetrakis(triphenylphosphine)palladium(0) (Pd(PPh 3 ) 4 ) was purchased from Strem Chemicals and used without further purication. 2,7-Dibromo-9,9-bis(5-bromopentyl)-9H-uorene, 29 2,7-dibromo-9,9-bis(8-bromooctyl)-9H-uorene, 30 and 1,1 0 -((2,7-dibromo-9H-uorene-9,9-diyl) bis(hexane-6,1-diyl))bis(2-phenyl-1H-benzo[d]imidazole) 23 were prepared according to literature procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Tetrakis(triphenylphosphine)palladium(0) (Pd(PPh 3 ) 4 ) was purchased from Strem Chemicals and used without further purication. 2,7-Dibromo-9,9-bis(5-bromopentyl)-9H-uorene, 29 2,7-dibromo-9,9-bis(8-bromooctyl)-9H-uorene, 30 and 1,1 0 -((2,7-dibromo-9H-uorene-9,9-diyl) bis(hexane-6,1-diyl))bis(2-phenyl-1H-benzo[d]imidazole) 23 were prepared according to literature procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Amongst the various interlayer materials demonstrated, polymer electrolytes have been often used because their permanent dipoles play a significant role in shifting the work function of the metal oxide electron transporting layer through the formation of local dipoles. It has also been reported that the oxygen vacancies present in the metal oxide buffer layers can be healed through the incorporation of bromine anions (bromides) present in various polyelectrolyte layers such as fluorene‐based and perylene/naphthalene diimide‐based polyelectrolytes and cationic quaternary ammonium‐based small molecules . Despite the significant promise, however, the number electrolyte materials investigated to date for OPV applications is limited to a few families.…”
Section: Introductionmentioning
confidence: 99%
“…Each binding energy was obtained from previous studies. [1], [8][9] As seen in Fig. 3 (b) and (c), the O L peak increased in ZRS 3% and decreased in ZRS 7%.…”
Section: Resultsmentioning
confidence: 58%
“…The ZnO NPs were synthesized by a previously used method. [1] Next, transmission electron microscopy (TEM) and X-ray diffraction (XRD) analysis was conducted to investigate the size and crystal structure of the ZnO NP only and ZRS. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation